The Effect of Motivation and Performance Evaluation on Employee Job Satisfaction of PT Asuransi Central Asia Cikini Jakarta Branch - Arfi, Nurul Hanny Ananda; Yanti, Vera Agustina; Rafik, Ahmad (Review: Journal of Multidisciplinary in Social Sciences, 2024)
PT Asuransi Central Asia (ACA) is a company engaged in general insurance, which was established on August 29, 1956. PT Asuransi Central Asia (ACA) is one of the national insurance companies with the largest number of assets, which currently reaches IDR 8.73 trillion. PT Asuransi Central Asia's (ACA) flagship insurance products are OTOMATE (motor vehicle insurance), ASRI (Ideal Home Insurance), and microinsurance products such as Dengue Fever Insurance. PT Asuransi Central Asia (ACA) also has other products that suit the needs of the community, namely property insurance, construction, transportation, ship frame, New Travel Safe (travel insurance), Medi+ (health insurance), Wellwoman (female cancer insurance), financial insurance, personal accident insurance, plant insurance and other insurance products. This research is a quantitative research, with the data collection technique used is a questionnaire. The sample in this study is 30 respondents. The data in this study was processed using SPSS software version 24. The results of this study show that motivation (X1) has a positive and significant influence on employee job satisfaction with a significance level of 0.000, performance evaluation (X2) has a positive and significant effect on employee performance with a significant level of 0.006, motivation and performance evaluation together have a positive and significant influence on employee job satisfaction with a significance level of 0.000 or 0%.